Parental expressed emotions and depression among adolescents: The mediating role of emotion regulation - Nurany, Putri Nabhani; Adiyanti, Maria Goretti; Hassan, Zainudin (Psikohumaniora: Jurnal Penelitian Psikologi, 2022)
Adolescence is a phase in life that is prone to depression. Depression in adolescents can be influenced by their family context, which can involve high parental expressed emotions and low emotion regulation among adolescents. This study aims to reveal the relationship between parental expressed emotion and adolescents’ depression, as mediated by emotional regulation in adolescents. The measuring instruments used are depression scales, the scale of adolescent emotional regulation and the scale of perceived parental expressed emotion. The participants were 212 adolescents who were identified using the purposive sampling technique. Analysis of the research data was made using simple mediation models with PROCESS. The results show a relationship between maternal expressed emotion and depression in adolescents, fully mediated by adolescent emotional regulation (BootLLCI = .030, BootULCI = .083, B = .055). There is also a relationship between fathers’ expressed emotion and depression in adolescents, partially mediated by adolescent emotional regulation (BootLLCI = .027, BootULCI = .073, B = .048). The results of the study could provide an alternative explanation of the dynamics of the relationships between fathers, mothers and adolescents. In addition, the findings emphasize the importance of adolescent emotion regulation.